2018
DOI: 10.18203/2320-1770.ijrcog20184937
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the level of serum uric acid in patients of pre-eclampsia and their comparison with levels in normotensive pregnancy

Abstract: Background: Pre-eclampsia is one of the major causes of maternal and perinatal morbidity and mortality. There are various parameters to evaluate pre-eclampsia. S.uric acid levels is one of the important biochemical markers in pre-eclampsia. The objective of current study is to compare the levels of S.uric acid in pre-eclamptic patients and normotensive patients.Methods: A total of 256 antenatal patients, consisting of two groups, 128 patients in each group diagnosed with pre-eclampsia (either earlier or during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…In a Nigerian population, Okonkwo and colleagues previously founda mean uric acid level of 6.05mg/dl in thirdtrimester normal pregnancies, which is comparable with the present study [25]. In pre-elamptic pregnancies, Ekun et al, Pramanik et al, Deshpande et al, Kasraeian et al respectively reported mean uric acid levels of 6.69, 6.27, 6.21, 6.20mg/dl comparable to the present study [28][29][30][31].…”
Section: Discussionsupporting
confidence: 89%
“…In a Nigerian population, Okonkwo and colleagues previously founda mean uric acid level of 6.05mg/dl in thirdtrimester normal pregnancies, which is comparable with the present study [25]. In pre-elamptic pregnancies, Ekun et al, Pramanik et al, Deshpande et al, Kasraeian et al respectively reported mean uric acid levels of 6.69, 6.27, 6.21, 6.20mg/dl comparable to the present study [28][29][30][31].…”
Section: Discussionsupporting
confidence: 89%